Small firms as agents of sustainable change. (March 2021) - Nesterova, I.
Highlights: Transition towards a strongly sustainable, post-growth society is required. Agents of change transform structures. Small firms can be agents of change via adopting practices in line with a strongly sustainable, post-growth economy. A set of potential practices derived from primary data is presented. Adoption of such practices does not suffice, humans' being in the world needs to change. Abstract: For the majority of human existence as hunter-gatherers people managed to co-exist with nature. Historically, the impact of human economy on the environment, compared to the impact of natural forces, was small. Progression of human economies towards agriculture and industrial, fossil fuel powered, and growth orientated economies saw humanity transitioning to a state of environmental destruction and multiple species on the brink of extinction. To avoid collapse and sustain life on Earth, a transformation of economies by agents instead of the reproduction of current structures is urgently required. A new vision of economy should be based on the principles of strong sustainability and post-growth. This paper identifies "radical" (pro-environmental, pro-social, and values driven) small firms as agents of change towards such new economy. It aims to (1) identify a set of practices informed by primary data from seven in-depth case studies of radical British small firms carried out in Spring-Autumn 2018 which may assist with operationalisation of sustainable change, and (2) outline a path for facilitation of these practices.